Italy's labour market reforms of 2012: did they reduce unemployment? - Piazza, Gabriele; Myant, Martin (Brussels, 2015)
"This Working Paper critically analyses Italy’s labour market reforms of 2012 (Fornero Reform). It focuses especially on a measure to cut unemployment and labour-market dualism by reducing the protection against dismissal enjoyed by permanent employees.